Self-esteem, resilience, perceived social support and attitude towards seeking counseling among pre-university students in a university in Malaysia - Sukumaran, Puspha (2019)
The current study aims to assess the attitudes towards seeking psychological help and identify how it correlates with psychological variables such as selfesteem, resilience and perceived social support among Malaysian university students. It is hypothesized that self-esteem, resilience and perceived social support would have a negative influence on help seeking attitudes. This study investigates the relationship between three independent variables and a dependent variable by using quantitative survey techniques. A survey enables researchers to see the correlation between factors, test multiple hypotheses and answer research questions. Furthermore, survey also enables researcher to draw generalizations concerning gathered data from the sample population. This study’s design is a combination of descriptive and correlational studies. Descriptive studies is used to assess the general level of self-esteem, resilience and perceived social support, t-test is used to establish the difference of each variable according to specific demographic data whereas correlational analysis was used to assess relationship between the independent variables and dependent variable of this study. Random sample selection method was used to recruit 260 respondents for this study. The questionnaires used in the study are Rosenberg Self-Esteem Scale (SES), Connor-Davidson Resilience Scale (CD-RISC), Multidimensional Scale of Perceived Social Support (MSPSS) and Attitudes toward Seeking Professional Psychological Help Scale (ATSPPHS). Data were analyzed using descriptive statistics, t-test, Pearson’s correlation analysis and multiple regression analysis. The research findings show that majority of students had moderate level of self-esteem (80.4%) and resilience (79.4%) and high level of perceived social support (73.5%). Majority of students also reported moderate level of attitudes towards seeking counseling (83.5%). The finding of this study manifests a negative correlation between self-esteem on attitudes towards seeking counseling. A positive correlation was established between perceived social support and attitudes towards seeking counseling. Resilience shows no correlation with attitudes towards seeking counseling. Further analysis using multiple regressions reveals that only self-esteem and perceived social support significantly predict attitudes towards seeking counseling. The results from this study will thus help to develop new interventions for campus health services in helping their students adapt and face challenging situations. It has implications for counselors who are working with young adults in detecting factors that prevent them from seeking psychological help in an effort to encourage their help seeking attitudes. Policy makers are able to gain insight on how to promote the overall counseling services by identifying disabling factors.